An additional case of Hennekam lymphangiectasia–lymphedema syndrome caused by loss‐of‐function mutation in ADAMTS3. Issue 12 (18th November 2018) - Scheuerle, Angela E.; Sweed, Nathan T.; Timmons, Charles F.; Smith, Erica D.; Alcaraz, Wendy A.; Shinde, Deepali N.
Abstract : Hennekam lymphangiectasia–lymphedema syndrome (HKLLS) is a genetically heterogeneous lymphatic dysplasia with characteristic of facial dysmorphism, neurocognitive impairments, and abnormalities of the pericardium, intestinal tract, and extremities. It is an autosomal recessive condition caused by biallelic mutations in CCBE1 (collagen‐ and calcium‐binding epidermal growth factor domain‐containing protein 1) (HKLLS1; OMIM 235510) or FAT4 (HKLLS2; OMIM 616006). CCBE1 acts via ADAMTS3 (a disintegrin and metalloprotease with thrombospondin motifs‐3 protease) to enhance vascular endothelial growth factor C signaling. There is report of one family supporting mutations in ADAMTS3 as causative for the phenotype labeled as HKLLS3. Here, we report an additional case of HKLLS that appears to be associated with homozygous nonsense mutation of ADAMTS3 .